PENGGUNAAN METODE PEMBELAJARAN KONTEKSTUAL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS SISWA KELAS III A SD NEGERI 02 KUNDUR - Raja Usman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This research is done because the still low student's IPS score is 62. Learning process in favor of the teacher is not on the student side. The subject matter that is delivered is the environment and implement the cooperation of third grade students of SD Negeri 02 Kundur. Type of research, classroom action research (PTK). The study was conducted in two cycles. Prior to carrying out the action, a preliminary test is conducted to find out how far students have knowledge. Learning method uses contextual teaching and learning (CTL) method. Data collection techniques by making RPP, Observation, action, reflection, and evaluation while the technique of data analysis is by observation techniques, interviews, results of relection, and evaluation. The research subjects of third grade students of SD Negeri 02 Kundur, consist of 13 women, and 14 men. Prasiklus 72.59 did not complete 37,04% and 63,96% complete, cycle I, 77,70 not 55,56% complete and complete to 44,44% and cycle II increased to 100%. Total prasiklus value of 1959 lowest 66 and 90 highest, cycle I total value 2098, low 65 and highest 93, cycle II number 2280, lowest score 70 and highest value 95. So the use of CTL method can improve student learning result of SD Negeri 02 Kundur.